(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper introduces four classes of continuous multifunctions defined from an ideal topological space into a bitopological space, namely upper almost quasi τ^(σ_1,σ_2)-continuous multifunctions, lower almost quasi τ^(σ_1,σ_2)-continuous multifunctions, upper weakly quasi τ^(σ_1,σ_2)-continuous multifunctions and lower weakly quasi τ^(σ_1,σ_2)-continuous multifunctions. Moreover, several characterizations of upper almost quasi τ^(σ_1,σ_2)-continuous multifunctions, lower almost quasi τ^(σ_1,σ_2)-continuous multifunctions, upper weakly quasi τ^(σ_1,σ_2)-continuous multifunctions and lower weakly quasi τ^(σ_1,σ_2)-continuous multifunctions are established. Furthermore, the relationships between almost quasi τ^(σ_1,σ_2)-continuity and weak quasi τ^(σ_1,σ_2)-continuity are discussed.